CORE OUTCOME SETS AND DENTAL PATIENT REPORTED OUTCOMES - LAMONT, THOMAS J.; CLARKSON, JAN E. (The journal of evidence-based dental practice, 2022)
In clinical research, outcomes are the results or ‘endpoints’ that are measured to assess whether clinical interventions have been successful or whether one treatment works better than another. There are a vast number of outcomes that have been reported in dental trials; the number, diversity and questionable relevance of these outcomes can lead to research wastage. Ultimately, this can lead to uncertainty for patients and dental professionals as to the most effective prevention and treatment options available as the evidence available may not use outcomes important to them. This article introduces the reader to core outcome sets (COS), covering the background to this area of research; their purpose and role; as well as the methodology of development. The authors reflect on their experience of leading the development of a core outcome set for periodontal trials and we highlight other dental COSs already developed and their inclusion of dental Patient Reported Outcomes (dPROs).